1959
DOI: 10.1111/j.1365-2494.1959.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical Composition and the Loss of Nutrients in Tripoded and Swath‐cured Hay

Abstract: The changes in chemical composition during haymaking, the loss of nutrients in the field and during storage, and the nutritive value of swath-cured and tripoded hay were compared. In good weather no advantage was gained by tripoding the hay. The nutritive value of the hays made by the two methods was similar and the loss of dry matter in the field slightly lower in the swath-cured hay. In a bad season, however, the nutrient loss in the swath-cured hay greatly exceeded that occurring in the tripoded hay and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1960
1960
1985
1985

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Wetting increased hay ADF concentration in every case. Wetting effects on hay ADF concentrations in this study are similar to those reported for crude fiber (CF) by Murdoch et al (1959) with fieldcured hay. An alfalfa-meadow fescue (Festuca pratensis Huds.)…”
Section: Acid Detergent Fibersupporting
confidence: 86%
“…Wetting increased hay ADF concentration in every case. Wetting effects on hay ADF concentrations in this study are similar to those reported for crude fiber (CF) by Murdoch et al (1959) with fieldcured hay. An alfalfa-meadow fescue (Festuca pratensis Huds.)…”
Section: Acid Detergent Fibersupporting
confidence: 86%
“…A number of workers have reported DM losses of about 3% per day during wilting (4,15,18,42,43,44,67), although much smaller losses (67,80) and larger losses (67,68) have also been reported. Other studies have shown no net change in DM during wilting (25) or DM gains (45,69).…”
Section: The Field Stagementioning
confidence: 99%
“…Estimates of the losses that occur during haymaking have been made by Fleishmann (3), Davis et al (1), Murdoch (12), Murdoch et al (13), Kormos and Chestnutt (10,11), while Watson and Nash (17) cite a number of other estimates. These estimates show a range of values of from 2 to 25 % loss.…”
Section: Introductionmentioning
confidence: 99%